Search 75,919 tutors
FIND TUTORS
Ask a question
0 0

solve the equation 11=y-9

Tutors, please sign in to answer this question.

4 Answers

To solve this equation, we need to get y alone on one side of the equal sign. To do this, we need to move the - 9 over to the left side. This means adding 9 to both sides of the equation.

  11 = y - 9

+ 9      + 9

  20 = y - 9 + 9

The - 9 and + 9 cancel out to 0, so we get 20 = y.

To check, we can always plug the value we get for the variable into the original equation.

11 = y - 9     ->     11 = 20 - 9     ->     11 = 11     It checks out! 

11=Y-9

You need to get the variable by itself, so you must remove the 9 from that part of the = sign to the other side since there is a number there without a variable. To do this you must add 9 to both sides of the equation. You are left with 

11 + 9 = Y

Add 11 and 9 to get 20. 

So 20 = Y

 

old fashion

11=y-9

when you cross over the bridge (=) the sign changes

take the -9 over the bridge

11+9 = y

20=y or y=20 

ANSWER   Y=20

 Proof

11+9 = y

when Y = 20

then  11+9 = 20

         20     = 20

 

or 11 = y-9

substitute Y  = 20

you get

11 = 20-9

11 = 11

looks like you're just solving for y... in which case, add nine to both sides and you get y = 20